Ways of effective use of financial resources of the fund for reconstruction and development of the Republic of Uzbekistan - Khaydarov, Kh.; Jumaniyazov, T. («Академик Е.А. Бөкетов атындағы Карағанды университеті» КЕАҚ баспасы, 2021)
This article examines and analyzes the criteria for maximum transparency, which is the main criterion for evaluating the effectiveness of sovereign funds. Two globally recognized methods for assessing the maximum transparency of sovereign wealth funds have been analyzed. The Santiago Principles and the Linaburg-Madwell Transparency Index, approved by 26 member countries of the International Monetary Fund and based on generally accepted rules, have been studied and analyzed in detail. Foreign experience in ensuring maximum transparency of sovereign wealth funds has been studied. A number of problems in ensuring the maximum transparency of the Fund's activities, which are the main criteria for assessing the effectiveness of the Fund for Reconstruction and Development in our country, were analyzed, scientific, and practical suggestions and recommendations were made to ensure maximum transparency of the Fund's activities.
Keywords: sovereign fund; Fund for Reconstruction and Development; Transparency Index; investment; economic effectiveness; investment projects; Linaburg-Madwell Transparency Index